Bridging information and knowledge using codification technology in requirements elicitation process - Che Pa, Noraini; Hassan, Sa'adah (Universiti Utara Malaysia, 2012)
Indeed, knowledge is very important for the organization. Tacit knowledge is the main source for explicit knowledge. Therefore, the tacit knowledge in organizational resources should effectively recognize and consequently explicitly represented. In the context of software requirements elicitation, organizations need to identify and allocate the knowledge during communicating for software requirements. Two categories of knowledge that involved are knowledge about the requirements and knowledge about the domain for which software being developed. Knowledge codification is proposed as a routine for seeking knowledge inputs that embodies in software requirements elicitation process and converting them on document context. As a result, the knowledge codification routine allows the building of the knowledge repository for use and reused in support of sustain software development. This paper offer a knowledge codification routine that categorized organizational resources into human, software, infrastructure and techniques as an input into explicit knowledge during requirements elicitation process.